2018
DOI: 10.1007/s10689-018-0078-2
|View full text |Cite
|
Sign up to set email alerts
|

Discussions about predictive genetic testing for Lynch syndrome: the role of health professionals and families in decisions to decline

Abstract: Unaffected relatives of individuals with Lynch syndrome can be offered predictive genetic testing to guide surveillance recommendations. The decision-making process of those who decline testing, particularly those who do not attend a clinical genetics service, is poorly understood. We have addressed this gap by interviewing 33 individuals from Lynch syndrome mutation-carrying families, unaffected by cancer, who declined predictive genetic testing. Here, we analyse the data provided by 20 participants who unequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Participants expressed concerns about financial implications associated with genetic testing and subsequent risk‐reducing interventions and insurance implications. These concerns are well documented 17,31,32 . Our study occurred before protective genetic discrimination regulations were introduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants expressed concerns about financial implications associated with genetic testing and subsequent risk‐reducing interventions and insurance implications. These concerns are well documented 17,31,32 . Our study occurred before protective genetic discrimination regulations were introduced.…”
Section: Discussionmentioning
confidence: 99%
“…To provide effective decision‐making support to affected individuals, healthcare providers must understand facilitators and barriers associated with these decision‐making processes. To date, Australian studies have restricted decision‐making research to those already commencing LS testing and/or are confirmed carriers 10,14–18 . CRC is the second most common cancer in Australia, 19 and universal genetic testing for LS on CRC may eventually become cost‐effective 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Strengths of the study include an experienced and diverse investigator group from across Australia that has published extensively together in the area [1,34,70,[73][74][75][76][77][78], and built upon previous research over two decades from some of the group members [8, 42, 46-48, 77, 79-84]. The project was made possible by an Australian government grant which was endorsed by the Victorian Department of Health & Human Services, Human Genetics Society of Australasia and over 20 other project partners, reflecting its widespread support and significance.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s, numerous studies in North America, the United Kingdom, Europe and Australia have described concerns regarding GD. These concerns were voiced by at-risk clinical patients [29][30][31][32][33][34][35][36][37][38][39], support groups [40], and the general public [41]. Some consumers reported feeling coerced into having genetic testing to make themselves eligible for insurance or reduce premiums [42].…”
Section: Consumersmentioning
confidence: 99%
“…It is known a long time that carrier subjects of pathogenetic mutation in a MMR gene undergone to recommends annual surveillance colonoscopy from age 25 years (51). In order to include the mutation carriers in the endoscopy surveillance programs more suited to them, a crucial point is represented by correct definition of the pathogenecity of MMR genetic variants identified in the mutation detection analysis (52,53). Thus, this knowledge may helpful to improve the related-LS cancer prevention programs.…”
Section: Management Of Lynch Syndrome Patient With Crcmentioning
confidence: 99%